ANALISIS PENGARUH TRANSFORMATIONAL LEADERSHIP DAN KOMPETENSI TERHADAP KINERJA KARYAWAN DENGAN CORE VALUES AKHLAK SEBAGAI VARIABEL INTERVENING DI KEBUN SEI KEBARA - Judha Iskandar; Retna Astuti; Erwin Nyak Akoeb; Angga Dwi Kelana Putra (JURNAL AGRIMANSION, 2025)
Sei Kebara Plantation is one of the plantations that contributes significantly to PTPN IV Regional 1. Sei Kebara Plantation PTPN IV Regional I was named the best plantation in the Plantation Holding Company in 2022 with a productivity of 30,304 kg/ha. The performance achievement for 2024 is 27,167 kg/ha and the target for 2025 is 35,350 kg/ha. Therefore, good leadership and competent human resources are needed to achieve these targets. One form of leadership style that is the most important part in driving the dynamics or changes in an organisation is transformational leadership. At the same time, competencies, including knowledge, skills, and attitudes/work ethics, are consistently linked to employee performance. The researcher aims to analyse transformational leadership and competence in relation to employee performance through the core values of AKHLAK at the Sei Kebara Plantation of PTPN IV Regional I. This research method uses a quantitative approach reinforced with descriptive qualitative data using a questionnaire and Structural Equation Modelling data analysis with a sample size of 80 employees. The results of the study indicate that only the variable directly related to Core Values of Morality indicates that an increase in competence does not contribute directly to the strengthening of moral values, while the other variables contribute directly and significantly, both directly and indirectly.